1997
DOI: 10.1055/s-2008-1064072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Neuromotor Processes of Swallowing

Abstract: Isolated swallowing difficulties are present in a substantial percentage of elderly adults. Most have no known medical basis, although some may be caused by underlying, but undetected, medical conditions. Others may result from conditions that indirectly affect swallowing. After an overview of the neuroanatomy and neurophysiology of swallowing, this article reviews findings on changes in swallowing that accompany aging. Some of the differences reported have failed to be replicated consistently, and other chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Normal pharyngeal swallowing function is largely reflexive in nature and coordination is required for adequate airway protection. 7 Ren studied vocal fold closure during swallowing and found no difference in the duration of vocal fold closure between old and young subjects without complaints of dysphagia. 8,9 Rademaker, on the other hand, studied a group of women over the age of 60 without dysphagia and found an increased duration of laryngeal closure and elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Normal pharyngeal swallowing function is largely reflexive in nature and coordination is required for adequate airway protection. 7 Ren studied vocal fold closure during swallowing and found no difference in the duration of vocal fold closure between old and young subjects without complaints of dysphagia. 8,9 Rademaker, on the other hand, studied a group of women over the age of 60 without dysphagia and found an increased duration of laryngeal closure and elevation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that individuals over the age of 65, on average, swallow more slowly than people under the age of 45 (Sonies et al 1984; Tracy et al 1989; Sonies 1992; Robbins et al 1992; Logemann et al 2000). Other reported age-related changes include: increased lingual connective tissue resulting in reduced masticatory strength and a longer oral phase (Jaredah 1994); extra lingual movements during bolus formation (Caruso and Max 1997); reduced lingual pressure (Shaker and Lang 1994); increased pharyngeal residue following the swallow (Tracy et al 1989; Robbins et al 1992); and reduced coordination of the oral and pharyngeal phases of swallowing (Tracy et al 1989). Furthermore, as lingual driving force is reduced with age, there is an increased likelihood of bolus retention in the valleculae (Dejaeger et al 1997), putting the elderly patient at risk of post-swallow aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…The upper ceiling of 65 was used in order to minimize the effect of age as a confounding variable. Swallowing impairments occur in all age groups with the elderly representing one of the largest groups [17,18] . Individuals under 18 were not included as the presentation of the virus has been found to be different in adults when compared to children [19] , and the focus of the study was on the adult population.…”
Section: Research Participantsmentioning
confidence: 99%